Relación entre el consumo de alimentos y dislipidemia en pacientes adultos del Hospital General Babahoyo (IESS), Los Ríos, octubre 2019 – marzo 2020. - Caicedo Toaza, Ivonne Michelle (2020)
This study titled relationship between food intake and dyslipidemia in adult patients at the Hospital General Babahoyo (IESS), Los Rios, October 2019 - March held aimed at determining the relationship between food intake and dyslipidemia in adult patients of the Hospital General Babahoyo (IESS). In the investigation of additional deductive and analytical methods were applied to it an applied transverse and observational research, which also presents an approach to quantitative since the frequency of food consumption, data specifically laboratory lipid profile shows that it is in the medical records of patients and are related to dyslipidemia as they are cholesterol and triglycerides, one sample of 217 adults who frequently attend external consultation in nutrition and dietetics service of the hospital was also used. The techniques adapted were the survey and direct observation through instruments "frequency of food consumption" which is among the main findings are that most of the population has a high saturated fat intake with 44% and processed foods with 20%, while the healthy foods that have great nutritional value as vegetables, fruits and nuts have an infrequently in consumption. In addition, a questionnaire form was added to understand the level of patients' knowledge about the disease, habits and food preparation mode, Also a registration for the lipid profile. Therefore, in conclusion it was established that the presence of dyslipidemia in patients is because there is a close relationship between eating habits and elevated cholesterol and triglycerides because of improper lifestyle, lack of knowledge and misfeeds.